THE INTERDEPENDENCE BETWEEN HUMAN AND NATURE IN CRAIGHEAD JEAN GEORGE'S MY SIDE OF THE MOUNTAIN - Sugiarto, Tri; Purbani, Widyastuti (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2019)
(Title: The Interdependence Between Human and Nature in Craighead Jean George's